نجم الدین ایوب (٥٦٨ ه / ١١٧٢م) - الدین, أ.د. عطا عبدالرحمن محی (Sulaimani Journal for Humanities, 2021)
Elzinkeen rule covers an area of significant history of Egypt and some parties in the Levant and Maghreb, but historical studies on affected and complexity of subject matter did not disclose some important aspects of the history, especially regarding penetration of Ministers to examine the figures and the men Altnfven powerful prince and pimp if we say that the son of the Kurdish Najmeldin Ayubi is one of those men strong powerful leading role since playing in his distinctive for important posts in the state zinkeen and also As a protector of the fortress of the city of Tikrit until the year (532AH-1137AD)in Iraq, in the zinkeen state, whether when he was the governor of Baalbek (534 AH-541AD/1139-1145AD)or after the became governor of Damascus and remained there for more than twenty-five years (541AH-565/1145-1169AD). Then he moved to Cairo and that the historians They agree to define his most important characteristic in running the affairs of his country, that he was a just and benevolent man, firm in implementing laws and imposing order, and they repeat the saying that his leadership qualities are vital. Such as courage, firmness, strong will, and wisdom in dealing with problems and others. We have seen his role in the unification of the Levant in the year(549AH-1154AD) as well as the continuity of peace between Egypt and the Levant in the year (567 AH-1171 AD). He also loves charitable work to serve Islam and Muslims, so he established inhabitation in Baalbek and Damascus, and finally we stay that Ayubs wisdom, sophistication, and his brother Sherkos inconceivable courage will have the greatest role in shaping their future.